Correlations, genetic and phenotypic parameters in quantitative and qualitative traits of Swietenia macrophylla in Ucayali, Peru - Revilla-Chávez, Jorge M. (2024)
The speed of growth in height of Swietenia macrophylla stands out in terms of resistance to attack by the Hypsipyla grandella borer and the selection of fast-growing families can make commercial plantings viable. The characters height, diameter, number of leaves and stem form of trees from 4 families of S. macrophylla, aged 47.5 months, planted in Ucayali, Peru, were used to investigate the possibility of selecting fast-growing genotypes. The average heritability (h2m) and selective accuracy (Acprog) between families were moderate for total height (Ht: h2m: 0.407; Acprog: 0.638) and commercial height (Hc: h2m: 0.472; Acprog: 0.687), in addition to Hc positively correlating with susceptibility to the drill attack. The stem form showed statistical differences between families and great h2m (0.984) and Acprog (0.921). The genetic (rg) and phenotypic (rf) correlations between traits showed that a selection of individuals with greater heights will generally result in greater growth in diameter, number of leaves and better stem form. The study highlights the importance of selecting families with fast growth in height and straight stems to enable, improve the quality and increase the productivity of commercial plantations with the species.